2018
DOI: 10.1371/journal.pgen.1007791
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral origin of ApoE ε4 Alzheimer disease risk in Puerto Rican and African American populations

Abstract: The ApoE ε4 allele is the most significant genetic risk factor for late-onset Alzheimer disease. The risk conferred by ε4, however, differs across populations, with populations of African ancestry showing lower ε4 risk compared to those of European or Asian ancestry. The cause of this heterogeneity in risk effect is currently unknown; it may be due to environmental or cultural factors correlated with ancestry, or it may be due to genetic variation local to the ApoE region that differs among populations. Explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 136 publications
(176 citation statements)
references
References 43 publications
10
163
3
Order By: Relevance
“…The heterogenous risk effect of the ApoE gene across the populations is suggested to be correlated with the ancestral background local to the ApoE gene. Thus, to examine the ancestral background in our dataset we calculated the average ancestry proportions at the ApoE by taking the average of the local ancestry estimates around the ApoE gene (from 44 Mb to 46 Mb on chromosome 19) 15 . The pipeline to calculate the global and local ancestries was developed by our group using R and Python scripts.…”
Section: Assessment Of Genetic Ancestrymentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogenous risk effect of the ApoE gene across the populations is suggested to be correlated with the ancestral background local to the ApoE gene. Thus, to examine the ancestral background in our dataset we calculated the average ancestry proportions at the ApoE by taking the average of the local ancestry estimates around the ApoE gene (from 44 Mb to 46 Mb on chromosome 19) 15 . The pipeline to calculate the global and local ancestries was developed by our group using R and Python scripts.…”
Section: Assessment Of Genetic Ancestrymentioning
confidence: 99%
“…The association of ApoE with AD risk differs between populations and is not clearly established in groups of Amerindian (AI) descent. The strongest association of ApoE and AD risk has been observed in East Asian (EA) populations (ε3/ε4 odds ratio OR: 3.1-5.6; ε4/ε4 OR: 11.8-33.1) followed by non-Hispanic White (NHW) populations (ε3/ε4 OR: 3.2; ε4/ε4 OR: 14.9) 8,9 . Its effect is weaker in African-descent and Hispanic populations (ε3/ε4 OR:1.1-2.2; ε4/ε4 OR: 2.2-5.7) [10][11][12][13][14] .Genetic studies examining the interaction of genetic ancestry and risk effect of the ApoE in Caribbean Hispanic populations (Puerto Rican and Dominican Republic) showed that the effect of the ε4 is correlated with the ancestral background around ApoE with the attenuated effect on African-originated haplotypes 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk for AD conveyed by the APOEε4 allele varies between populations, with a stronger risk for APOEε4 homozygotes in Non-Hispanic Whites (NHW) (Odds Ratio (OR) ~15) [3][4][5][6] than for African-Americans (AA) (OR~8) and Africans (OR~3 for) [3][4][5][6][7][8][9] . Recent studies have shown the lower risk in African and AA APOEε4 carriers is associated with the African local genomic ancestry (LA) around the APOEε4 allele 10 . As there are no distinct amino acid changes in APOEε4 between AA and NHW, we hypothesized that noncoding variants affecting gene expression are likely involved.…”
Section: Mainmentioning
confidence: 99%
“…To assess the LA, we phased our datasets (SHAPEIT version 229 ) using 1000 Genomes Phase 3 (1kGP) reference panel and used RFMix to infer LA at loci across the genome30 . We defined an initial region (chr19:44,000,000-46,000,000Mb) around the APOE locus that was broad enough to include potential enhancers, topological associated domains, and other regulatory factors while narrow enough to ensure contiguous LA blocks10 . After selecting the APOE LA region, we selected individuals homozygous for European (n=4) and African (n=4) local ancestry haplotypes.…”
mentioning
confidence: 99%
“…Although, the APOE e4 allele is a major risk factor for AD, odds ratios vary considerably among ethnic groups 42,43 , with the highest risk in East Asians 42,44 , followed by non-Hispanic Caucasians 42,45,46 and lowest in African ancestry populations 42,[47][48][49] . This may be the result of environmental factors, or population-specific genetic factors, with some evidence suggesting the latter 43 . Nonetheless, the odds-ratios derived from European studies of AD cannot be applied directly to non-European populations.…”
Section: Limitationsmentioning
confidence: 99%